Suara dari belantara : perbincangan tentang suasana politik di Malaysia - Shaari Isa, 1933- (Kuala Lumpur : Utusan Publications & Distributors Sdn Bhd, 2013)
On political issue in Malaysia.
Includes index.
In Malay.
Keywords: Politicians -- Malaysia; Malaysia -- Politics and government; Malaysia -- History